1984
DOI: 10.1152/ajpheart.1984.246.6.h747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thrombocytopenia on monocrotaline pyrrole-induced pulmonary hypertension

Abstract: Monocrotaline pyrrole (MCTP) causes lung injury, pulmonary hypertension, and right ventricular hypertrophy in rats. To determine if platelets are involved in the cardiopulmonary effects of MCTP, the response to MCTP was determined in thrombocytopenic rats. Blood platelet count was reduced to 10-20% of normal for 48 h by ip administration of an antirat platelet serum (PAS) prepared in the goat. Rats were treated iv with either MCTP 5 mg/kg or dimethylformamide vehicle and with either PAS or preimmune serum. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…This ex vivo investigation may assist in interpreting previous conflicting whole animal studies demonstrating that platelets can either maintain normal pulmonary membrane permeability (39), augment lung injury (12), have no effect on membrane permeability (40), or generate pulmonary hypertension in models of acute lung injury (15,41). In models of injury that generate oxidant stress, the antioxidant capacity of the platelets may determine whether they neutralize toxic oxygen metabolites before membrane injury occurs or whether they participate in pathogenetic events by releasing vasoactive substances that augment underlying membrane permeability defects.…”
Section: Discussionmentioning
confidence: 98%
“…This ex vivo investigation may assist in interpreting previous conflicting whole animal studies demonstrating that platelets can either maintain normal pulmonary membrane permeability (39), augment lung injury (12), have no effect on membrane permeability (40), or generate pulmonary hypertension in models of acute lung injury (15,41). In models of injury that generate oxidant stress, the antioxidant capacity of the platelets may determine whether they neutralize toxic oxygen metabolites before membrane injury occurs or whether they participate in pathogenetic events by releasing vasoactive substances that augment underlying membrane permeability defects.…”
Section: Discussionmentioning
confidence: 98%
“…MCT is metabolized in the liver and changed to the active form (monocrotaline pyrrole) which, after a single subcutaneous injection, injures vascular endothelium of pulmonary vessels within several hours (26), activates platelets within 1 week (27,28), and causes enhanced reactivity of pulmonary vessels to vasoconstrictive substances (29) and muscular hypertrophy of the media of pulmonary vessels (30). Mortality due to right cardiac failure begins 3 to 4 weeks after the injection and the survival decreases to about 30% by 6 weeks after the injection.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory lesions of pulmonary capillaries, arterioles and arteries induced by MCT con tain WBCs, and a large number of WBCs and elevation of eieosanoids are also seen in bronchoalveolar lavage fluid [9J. H ¡Hiker et al [7,8] studied MCT rats and found data that strongly pointed to a role of PLTs in the development of pulmonary hypertension. The purpose of the present study was to investigate the sequestration ofWBCs and PLTs in pulmonary' capillaries during the development of Sequestered Leukocytes and Platelets in Monocrotaline Pulmonary Hypertension pulmonary' hypertension and RV hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…A progressive rise in pulmo nary artery pressure and the development of right ventric ular (RV) hypertrophy appear to correlate with these pul monary vascular changes [4][5][6], Therefore, the type of pulmonary hypertension for which MCT-induced pulmo nary hypertension is used as a model need to be specified. In addition, time course studies in this MCT rat model have indicated that chronic lung inflammation precedes pulmonary hypertension and RV hypertrophy [7][8][9], In the present study, the sequestration of leukocytes (WBCs) and platelets (PLTs) in the pulmonary microvas culature was investigated by real-time confocal laser mi croscopy [10][11][12][13] tion of these cells to the development of cardiopulmonary changes in rats with MCT-induced pulmonary hyperten sion.…”
Section: Introductionmentioning
confidence: 99%